Challenges Associated with Informed Consent in Low- and Low-Middle-Income Countries - Upjohn, Melissa; Wells, Kimberly (Frontiers in Veterinary Science, 2016)
Obtaining informed consent from research participants is a generally recognized step of undertaking research. While the concept of informed consent is well understood in western research environments, it requires further consideration when reviewing studies involving humans and owned animals in low- and low-middle-income countries (LMICs), in order to take account of different social, educational, and research norms. Here, we identify some of the challenges that need to be considered, and how they might affect the process of obtaining informed consent. We explain the approach taken by an animal welfare non-governmental organization working in LMICs to addressing these challenges. There are also questions that reviewers might consider when commenting on work originating in this context.